Cord Blood as a Source of Natural Killer Cells - Mehta, Rohtesh S.; Shpall, Elizabeth J.; Rezvani, Katayoun (Frontiers in Medicine, 2016)
Cord blood (CB) offers several unique advantages as a graft source for hematopoietic stem cell transplantation (HSCT). The risk of relapse and graft-versus-host disease (GVHD) after cord blood transplantation (CBT) are lower than what is typically observed after other graft sources with a similar degree of human leukocyte antigen (HLA) mismatch. Natural killer (NK) cells have a well-defined role in both innate and adaptive immunity and as the first lymphocytes to reconstitute after HSCT and CBT, they play a significant role in protection against early relapse. In this article, we highlight the uses of CB NK cells in transplantation and adoptive immunotherapy. First, we will describe differences in the phenotype and functional characteristics of NK cells in CB as compared with peripheral blood. Then, we will review some of the obstacles we face in using resting CB NK cells for adoptive immunotherapy, and discuss methods to overcome them. We will review the current literature on killer-cell immunoglobulin-like receptors (KIR)-ligand mismatch and outcomes after CBT. Finally, we will touch on current strategiesfor the use of CB NK cells in cellular immunotherapy.